1996
DOI: 10.5547/issn0195-6574-ej-vol17-no2-5
|View full text |Cite
|
Sign up to set email alerts
|

Social Benefits of Financial Investment Support in Energy Conservation Policy

Abstract: This paper examines the costs and benefits of a Norwegian energy conservation program that provided financial support for investments in energy efficiency. Participants in the program included industry, commerce, public services and households. Evaluation of the program shows that about 70% of the participants were "free riders' who would have invested in efficiency improvements even in the absence of the program. The economic efficiency was further reduced by economic distortions caused by taxes needed to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Research in Norway indicates similar results: a direct rebound effect of about 40% for households and 10% for commerce (Haugland, 1996). In industry the extent of the direct rebound depends on the possibilities for substitution of inputs: it is higher in industries (such as metals) with limited substitution possibilities than in industries (such as chemical and mineral products) which have greater opportunities to adjust inputs (Grepperud and Rasmussen, 2004).…”
Section: Tablementioning
confidence: 74%
“…Research in Norway indicates similar results: a direct rebound effect of about 40% for households and 10% for commerce (Haugland, 1996). In industry the extent of the direct rebound depends on the possibilities for substitution of inputs: it is higher in industries (such as metals) with limited substitution possibilities than in industries (such as chemical and mineral products) which have greater opportunities to adjust inputs (Grepperud and Rasmussen, 2004).…”
Section: Tablementioning
confidence: 74%
“…This occurs where incentives are paid to those who would have bought efficient appliances in any case, thus increasing the cost to government of the incentive system [24]. In one notable study in Norway, 13Revised submission version 010812 single 050203 assessment of incentives for participation in an energy conservation program indicated that around 70% of those taking up the incentive would have undertaken the investment within two years in any case, without the incentive [29]. While careful policy design may seek to minimise the impact of free riders, it may in practice be very difficult to identify ex ante the likely takeup of an energy efficiency measure in the absence of a subsidy incentive.…”
Section: Incentivesmentioning
confidence: 99%
“…In particular, internal financial decision-making procedures vary largely across firms. As Graham and Harvey (2001) report, firms typically vary as to how 2 For instance, previous empirical work on the DSM program has focused exclusively on household decision-making and has not accounted for the role of observable information in relation to free riding (e.g., Malm, 1996;Haugland, 1996;Loughran and Kulick, 2004). The same holds for recent work on tax rebates for hybrid vehicles (Chandra et al, 2010;and Gallagher and Muehlegger, 2011).…”
Section: Introduction †mentioning
confidence: 82%
“…13 In the To determine the degree to which the use of observable characteristics may reduce the rent-incentive trade-off, we compiled a micro panel data set with information from Senter, which was supplemented with field data obtained from a survey among firms that were granted the subsidy between 1997 and 1999. Using the Senter database, we selected 20 technologies (see Table 2) on the basis of the following criteria.…”
mentioning
confidence: 99%